Juvenal's tenth satire - Murgatroyd, Paul (Liverpool University Press, 2017)
This is not a commentary on Juvenal 10 but a critical appreciation of the poem which examines it on its own and in context and tries to make it come alive as a piece of literature, offering one man's close reading of Satire 10 as poetry, and concerned with literary criticism rather than philological minutiae. In line with the recent broadening of insight into Juvenal's writing this book often addresses the issues of distortion and problematizing and covers style, sound and diction as well. Much time is also devoted to intertextuality and to humour, wit and irony. This is something new: building on the work of scholars like Martyn, Jenkyns and Schmitz, who see in Juvenal a consistently skilful and sophisticated author, this is a whole book demonstrating a high level of expertise on Juvenal's part sustained throughout a long poem (rather than intermittent flashes). This investigation of 10 leads to the conclusion that Juvenal is an accomplished poet and provocative satirist, a writer with real focus, who makes every word count, and a final chapter exploring 11 and 12 confirms that assessment. Translation of the Latin and explanation of references are included so that Classics students will find the book easier to use and it will also be accessible to scholars and students interested in satire outside of Classics departments.